Becoming A Superhuman (A Comparative Structural Analysis on Superheroes Movie): A Comparative Structural Analysis - Tami, Rosmah; Yahya, Ahsan Rezeki; Taufik, Muhammad (Journal of Islamic Culture and Literature (JICeL), 2023)
This study is a structural comparative analysis of two superhero movies Spiderman (2002) and Ironman (2008). Structure of a narrative can be seen from its surface or deep structure, and the one analysed here is the surface structure in order to find the deepest one. This article explores events undergone of the level the first is are the two movies have the same process in becoming superhero? The second question seeks to find the power source of the superhero’s. using Larsen and Johansen elaboration on semiotics’ structure and action of the narration, the article shows that the two movies basically use the same structural step in building the stories in three main elements namely the act to will, the knowledge, and the ability. The will to act